The Effect of Profitability, Leverage, Corporate Social Resposibility, and Institutional Ownership on Tax Aggressiveness - Isdianawati, Yosida; Fisher, Bobby (E-Jurnal Akuntansi, 2025)
Tax aggressiveness is a strategic issue of concern due to its potential to reduce state revenue through various corporate efforts to minimize tax burdens, whether through legal or illegal means. This study analyzes the effects of profitability, leverage, corporate social responsibility (CSR), and institutional ownership on tax aggressiveness in basic and chemical industry companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2023 period. Data from 132 companies were analyzed using panel data regression. Results show significant effects for profitability, CSR, and leverage, but not for institutional ownership.  Keywords: Tax Aggressiveness; Profitability; Leverage; Institutional Ownership